Frequency and duration of drug-free remission after 1 year of treatment with etanercept versus sulfasalazine in early axial spondyloarthritis: 2 year data of the ESTHER trial. Issue 7 (22nd March 2012) - Song, In-Ho; Althoff, Christian E; Haibel, Hildrun; Hermann, Kay-Geert A; Poddubnyy, Denis; Listing, Joachim; Weiß, Anja; Djacenko, Svetlana; Burmester, Gerd R; Bohl-Bühler, Martin; Freundlich, Bruce; Rudwaleit, Martin; et al.
Abstract : Purpose: The aims of this study were (1) to assess the frequency and duration of drug-free remission and efficacy of etanercept (ETA) treatment after flare in patients with early active axial spondyloarthritis who were treated with ETA (n=40) versus sulfasalazine (SSZ, n=36) for 48 weeks and (2) to analyse the efficacy of ETA treatment in patients in year 2 who did not reach remission at week 48. Method: At week 48, patients who reached study remission (Assessment of Spondyloarthritis international Society (ASAS) plus MRI remission) were followed up without active treatment up to 1 year. In case of a flare, patients were treated with ETA for another year. All patients who were not in ASAS plus MRI remission at week 48 were treated with ETA in year 2. Results: ASAS plus MRI remission at week 48 was reached significantly more often in ETA-treated compared to SSZ-treated patients (33% vs 11%, p=0.03). However, the flare rate was not different between these two groups: 69% in the ETA group versus 75% in the SSZ group. Only 8% of patients initially treated with ETA versus 3% of those initially treated with SSZ reached permanent drug-free remission (not significant). After treatment with ETA over 1 year, patients with flare showed an improvement in all clinical and imaging variables. Conclusion: Patients with axial spondyloarthritis treated with ETA over 1 year did not reach drug-free remission in a higher percentage compared to patients from a control group treated with SSZ.